Nutritional adequacy of a cows' milk exclusion diet in infancy. Issue 1 (2nd June 2016) - Maslin, Kate; Oliver, Erin M.; Scally, Karen S.; Atkinson, Josh; Foote, Keith; Venter, Carina; Roberts, Graham; Grimshaw, Kate E. C.
Abstract: Background: Infants with suspected cows' milk allergy are required to follow a strict milk exclusion diet which may lead to nutritional deficiencies, especially if not supervised by a healthcare professional. The aim of this study was to assess the nutritional adequacy of a cows' milk exclusion diet in a group of UK infants over a period of 6 months. Methods: Participants in this study are a subgroup of the Prevalence of Infant Food Allergy study, a prospective food allergy birth cohort study from the South of England. Each infant consuming a milk free diet, following advice from a specialist allergy dietitian, was matched to two control infants who were consuming an unrestricted diet, forming a nested matched case–control study. Detailed food diaries completed prospectively for 1 week per month over a 5 month period, were coded and analysed according to a standard protocol. Results: The diets of 39 infants (13 milk‐free and 26 controls) were assessed. Mean age at diet commencement was 14 weeks. Two of the eleven infants started on an extensively hydrolysed formula did not tolerate it and required an amino acid formula for symptom resolution. All infants had mean intakes in excess of the estimated average requirement for energy and the recommended nutrient intake (RNI) for protein, calcium, iron, selenium, zinc, vitamins A, C and E. Vitamin D intake was in excess of the RNI at all time‐points, except at 44 weeks of age. Across the study period, selenium intake was higher for infants consuming a milk free diet whilst vitamin C intake was higher for infants consuming an unrestricted diet. Differences were found between the two groups for protein, calcium, iron and vitamin E intakes at differing time points. Conclusion: This study demonstrated that although infants consuming a milk‐free diet have a nutritional intake that is significantly different to matched controls who are eating an unrestricted diet, this difference is not constant and it is not seen for all nutrients. Further research in infants without dietetic input is needed to explore the nutritional implications of unsupervised cows' milk exclusion diets.